2017
DOI: 10.1111/mmi.13718
|View full text |Cite
|
Sign up to set email alerts
|

The role of intrinsically disordered C‐terminal region of FliK in substrate specificity switching of the bacterial flagellar type III export apparatus

Abstract: The bacterial flagellar export switching machinery consists of a ruler protein, FliK, and an export switch protein, FlhB and switches substrate specificity of the flagellar type III export apparatus upon completion of hook assembly. An interaction between the C-terminal domain of FliK (FliK ) and the C-terminal cytoplasmic domain of FlhB (FlhB ) is postulated to be responsible for this switch. FliK has a compactly folded domain termed FliK (residues 268-352) and an intrinsically disordered region composed of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 74 publications
3
32
0
Order By: Relevance
“…The C‐terminal domain of a FliK homologue, YscP, of the Yersinia injectisome binds to the C‐terminal cytoplasmic domain of a FlhB homologue, YscU, to promote substrate specificity switching of the virulence‐associated type III protein export apparatus (Ho et al, ). Consistently, photo‐cross‐linking experiments have showed a direct interaction between FlhB C and the C‐terminal domain of FliK (FliK C ; Kinoshita, Aizawa, Inoue, Namba, & Minamino, ).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The C‐terminal domain of a FliK homologue, YscP, of the Yersinia injectisome binds to the C‐terminal cytoplasmic domain of a FlhB homologue, YscU, to promote substrate specificity switching of the virulence‐associated type III protein export apparatus (Ho et al, ). Consistently, photo‐cross‐linking experiments have showed a direct interaction between FlhB C and the C‐terminal domain of FliK (FliK C ; Kinoshita, Aizawa, Inoue, Namba, & Minamino, ).…”
Section: Introductionmentioning
confidence: 74%
“…Extragenic fliK suppressor mutations have been identified in FlhB CC but not in FlhB CN (Kinoshita et al, ; Kutsukake et al, ; Minamino, Ferris, Morioya, Kihara, & Namba, ; Williams et al, ), suggesting that FlhB CC is involved in the substrate specificity switching. Here, to clarify the role of the conserved residues of FlhB CC , Pro‐287, Pro‐311, Leu‐318, Ala‐319, Arg‐320, Leu‐322, Glu‐342 and Leu‐344, in the substrate specificity switching, we carried out mutational analysis of these residues.…”
Section: Discussionmentioning
confidence: 99%
“…When the hook length is too short, FliK is secreted out into the extracellular media. When the hook length reaches approximately 55 nm, the C-terminal domain of FliK binds to FlhB, one of the export gate component proteins, to induce conformational changes of FlhB and FlhA to switch the substrate specificity of the export apparatus [17][18][19][20][21][22]. The filament-type proteins form a complex with their specific cognate chaperones, which prevent premature aggregation and/or proteolysis of their cognates and help them associate with the flagellar protein export apparatus in the cytoplasm [23][24][25].…”
Section: Bacteria Strains and Plasmidsmentioning
confidence: 99%
“…Insertions and deletions in FliK N make the hook longer and shorter, respectively, suggesting that FliK N is a molecular ruler 42 . FliK N binds to FlgD and FlgE [43][44][45] , and deletion of residues 129-159 in FliK N reduces the binding affinity of FliK for FlgE, thereby producing longer hooks with the filament attached. This suggests that the interaction of FliK N with FlgE is required for proper hook length measurement 44 .…”
mentioning
confidence: 99%
“…1a) 40,46 . The core domain of FliK C binds to FlhB C to allow the flagellar protein export apparatus to switch its substrate specificity from rod-(FlgB, FlgC, FlgF, FlgG, FlgJ, FliE) and hook-type (FlgD, FlgE, FliK) to filament-type (FlgK, FlgL, FlgM, FliC, FliD) 11,12,28,45,47 . Genetic analyses of FliK CT have suggested that FliK CT controls the export switching activity of FliK C during hook assembly 45,47 .…”
mentioning
confidence: 99%